The Interplay of Cultural Dynamics within the Globalization Paradigm - Siregar, Iskandarsyah; Hsu, Forrest (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
Language serves as a manifestation of cultural values and acts as a guiding force in the trajectory of societal advancement. Consequently, language stands out as a crucial and compelling variable warranting systematic examination and scholarly scrutiny to ensure the preservation and advancement of civilization. In the Republic of Indonesia, Bahasa Indonesia stands as the official language, unifying a populace characterized by multiculturalism and ethnic diversity, in line with the ethos of the 1928 Youth Pledge Convention aimed at fostering national unity. However, there is a pressing concern regarding the waning prominence of Bahasa Indonesia. While the language remains in use, there is a noticeable trend of incorporating foreign terms into public discourse, often perceived as more prestigious. This study employs a descriptive qualitative approach, drawing upon literary sources and previous research findings. The proliferation of foreign language usage, considered more esteemed, poses a potential threat to the vitality of Bahasa Indonesia. Nevertheless, the current state of the language remains relatively secure. Bahasa Indonesia's endurance hinges on its adaptation to contemporary contexts and adherence to linguistic norms, coupled with ongoing refinement to meet the evolving needs and aspirations of society.